Exploring the Glycans of Euglena gracilis - Ellis C. O’Neill; Sakonwan Kuhaudomlarp; Martin Rejzek; Jonatan U. Fangel; Kathirvel Alagesan; Daniel Kolarich; William G. T. Willats; Robert A. Field (Biology, 2017)
Euglena gracilis is an alga of great biotechnological interest and extensive metabolic capacity, able to make high levels of bioactive compounds, such as polyunsaturated fatty acids, vitamins and β-glucan. Previous work has shown that Euglena expresses a wide range of carbohydrate-active enzymes, suggesting an unexpectedly high capacity for the synthesis of complex carbohydrates for a single-celled organism. Here, we present an analysis of some of the carbohydrates synthesised by Euglena gracilis. Analysis of the sugar nucleotide pool showed that there are the substrates necessary for synthesis of complex polysaccharides, including the unusual sugar galactofuranose. Lectin- and antibody-based profiling of whole cells and extracted carbohydrates revealed a complex galactan, xylan and aminosugar based surface. Protein N-glycan profiling, however, indicated that just simple high mannose-type glycans are present and that they are partially modified with putative aminoethylphosphonate moieties. Together, these data indicate that Euglena possesses a complex glycan surface, unrelated to plant cell walls, while its protein glycosylation is simple. Taken together, these findings suggest that Euglena gracilis may lend itself to the production of pharmaceutical glycoproteins.